КЛИНИКО-ИММУНОЛОГИЧЕСКИЕ АССОЦИАЦИИ ПРИ МЕТАБОЛИЧЕСКОМ СИНДРОМЕ - А. Ф. Салихова; Г. Г. Байбурина; Л. М. Фархутдинова; Л. Ф. Азнабаева (SINAPS LLC, 2014)
The article deals with the metabolic syndrome problem. The article deals with the results of studying the immune status of patients with the metabolic syndrome: cytokines level, the main classes of immunoglobulins, antibodies to β-cell of pancreas in serum of blood and their interrelation with violation of a carbohydrate exchange.